Associated factors of modern contraceptive use among women infected with human immunodeficiency virus in Enemay District, Northwest Ethiopia: a facility-based cross-sectional study - Yibeltal Bimrew Kebede; Tesfahun Taddege Geremew; Yohannes Mehretie; Ayenew Negesse Abejie; Liknaw Bewket; Endalkachew Dellie (BMC, 2019)
Abstract Background The prevention of unplanned pregnancy among women infected with human immunodeficiency virus (HIV) is critical for the prevention of mother-to-child transmission (PMTCT) of HIV. Of the prevention strategies, deployment of modern contraceptives is principal one. However, there were limited facts on utilization of modern contraceptives and associated factors among HIV infected women, in particular of resource-limited settings in Ethiopia. Hence, we aimed to quantify the proportion of modern contraceptive utilization and the possible related factors among women infected HIV. Methods A facility-based cross-sectional study was conducted on randomly selected 632 women infected with HIV from 05 February to 25 March 2018. Data on their treatment, socio-economic, and demographic background were collected through a structured interviewer administered questionnaire. Binary logistic regression model was fitted to identify the associated factors of modern contraceptive use among women infected with HIV. Result We found 61.4% (95% CI, 57.6-65.2) were using modern contraceptives. Greater than four family size (AOR:2.17; 95%CI: 1.31-3.59), family planning counseling service (AOR: 2.37; 95% CI: 1.44-3.91), discussing contraceptive issues with sexual partner (AOR: 1.76; 95% CI: 1.12-2.77), history of giving birth (s) (AOR:2.21; 95%CI:1.20-4.05) and World Health Organization (WHO) clinical stage III or IV (AOR: 3.59; 95%CI: 1.37, 9.44) were positively associated with modern contraceptives use, whereas, older age (AOR: 0.45; 95% CI: 0.24-0.81) and being widowed (AOR: 0.34; 95% CI: 0.14-0.83), abridged the chances of modern contraceptives use. Conclusion The prevalence of modern contraceptive use among women infected with HIV is low. Higher family size, counseling on contraceptives, discussing contraceptives issues with partner, history of giving births and WHO clinical stage III/IV were positively related with contraceptives use, whereas, older age and being widowed abridged the chances of contraceptives use among HIV infected women. Therefore, our findings support calls for the district health office and the antiretroviral treatment clinics of the resource-limited settings to work more on family planning counseling services and promoting more dialogues with sexual partners on modern contraceptives use.